Training on Making Desserts from Western Europe in Gerendeng Pulo Village - Etlivia Burianto; Nity Indrawan; Putri Cicilia Jusan (Return : Study of Management, Economic and Bussines, 2023)
Community Service is a person, group, or institution trying to make a positive contribution to society. Community service is often associated with higher education and research, where students and academics engage in activities that can use their knowledge and skills to help solve problems, improve well-being, and benefit society as a whole. PKM "Training on Making Desserts from Western Europe" due to the market for the sale of sweet foods from Western Europe, the purpose of the research is   to provide training on how to make sweet dishes from Western Europe in Gerendeng Pulo Village with the aim of improving the economy and meeting problems, namely by looking for sweet food cooking ideas at home and sweet food business ideas at affordable ingredient costs and teach them as the author collects the data of pre, post test and feedback from the community. The hope to be achieved is that the residents of Gerendeng Pulo Village can use the products and services they have learned, in order to provide benefits for them and increase their income through business ventures. The results shown that there is positive significant result about solving the problems faced by the people of  gerendeng pulo.